“La colisión de la administración de justicia comunal con la administración de justicia ordinaria en el delito contra la seguridad publica en la modalidad de tenencia ilegal de armas de fuego; En la etnia awajún, provincia de Rioja; Región de San Martín-2015” - Bardales Del Aguila, Lionel (2016)
The study aims to determine the factors involved in the collision of the administration of justice with ordinary communal administration in the crime against public security in the forro of illegal possession of firearms in the Awajún ethnicity of the province of Rioja, San Martín region. The research is descriptive, population and study sample confortned 458 inhabitants ofthis ethnic group, who were applied a survey; he meta 5 Heads or Apus of indigenous communities, 7 authorities linked to the ordinary courts: Judge not Legal Paz, the district govemor Awajún, the commissioners ofthe National Police Pardo Miguel (Orange) and Nueva Cajamarca, the Criminal Prosecutor of Nueva Cajamarca, the Director of the Public Defender of San Martín, the President of the Superior Court of San Martín. Records and sentences passed on culturally conditioned mistake and the case Wajajai Melvin Espinoza were analyzed for illegal possession of firearm. The results of the surveys of residents, interviews, literature and jurísprudence on the subject of study allow us to infer: that 91 % of respondents Awajun people use guns ( shotguns and trappers) for hunting, and community security as part of their custom and tradition, and Ap us heads interviewed said that the villagers do not know. the procedures for the registration of firearms, they just leam when they are operated by the National Police. 96% of people surveyed rely Apus the bosses and communities to resolve conflicts, 70% belíeved that cases of illegal possession of firearms should solve community justice, in general the higher rate of 71 % He prefers the communal justice, calling the ordinary courts of fair to poor between 55% and 14% and only a third said it was bad. The Commissioners of the National Police and Criminal Prosecutor, Awajún people believe that should be subject to the procedures established by the ordinary justice and indigenous justice must resolve minor cases in the case of illegal possession of firearms should treat the ordinary courts. Judge Legal Peaceforce, the District Govemor, the President of the Superior Court and the Director of the Public Defender of San Martín, agree in indicating that in these cases, must apply the common law and the requirements of art. 169, article 149 of the Constitution, Art. 15 of the Criminal Code on the error culturally conditioned, and the procedures established in the Protocol Coordination Justice Systems Intercultural approach. Villagers, Heads of native communities; the President of the Court and the Director of the Public Defender of San Martin; They agree on the creation of the Greater Community Council of Justice, with greater powers to resolve major cases including those of rape and murder; granting autonomy to the community justice. In conclusion: Despite the existence rules to resolve the conflict between the two types of justice; these remain: the absence of a sustainable training plan for judicial officers and Awajún population; the reigning doctrinal confusion among operators of justice on the powers of communal justice and ordinary justice, and misapplication of art. CP 15 "culturally conditioned mistake"; adding to it the wrong ideological and political ethnocentric conception of ethno-cultural superiority and discrepancies between integration-coordination-autonomy of the legal system.